Dispute Resolution in Foreign Investment: The Perspective of Latin American States and a Convergent Model - Carbajal Valenzuela, Christian Armando (2025)
This article analyzes the evolution of the foreign investment dispute settlement system in Latin America, highlighting the region's leading role in international arbitration. It also analyzes the effects of BITs and FTAs, as well as the criticisms of the traditional model. On the other hand, the Peruvian experience is contrasted with the preventive approach of the Brazilian model. It also discusses the reform proposals promoted by UNCITRAL. Finally, a convergent model that balances public and private interests is proposed.